2015
DOI: 10.1017/s1742170515000150
|View full text |Cite
|
Sign up to set email alerts
|

Understanding perennial wheat adoption as a transformative technology: evidence from the literature and farmers

Abstract: Perennial grain crops are an example of a 'transformative technology,' in which the functionality and science of the technology differ in a fundamental manner from conventional grain crops. A review of the literature indicates that the motivation for farmer adoption of transformative technologies is complex and poorly understood. At the same time, many studies have found concern and awareness about environmental issues to be significantly and positively correlated with the adoption of no-till agriculture, orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 59 publications
2
24
1
Order By: Relevance
“…Consistently, among all farmer participants, the theme emerged that grain yield matters. This finding is contrasting to the results of Adebiyi et al (2015) and Marquardt et al (2016) who found that perennial grain yield was of low importance to farmers interviewed. Yield matters particularly to farmers in regions where corn/soy cropping systems are dominant and productive.…”
Section: Grain Harvestcontrasting
confidence: 98%
See 2 more Smart Citations
“…Consistently, among all farmer participants, the theme emerged that grain yield matters. This finding is contrasting to the results of Adebiyi et al (2015) and Marquardt et al (2016) who found that perennial grain yield was of low importance to farmers interviewed. Yield matters particularly to farmers in regions where corn/soy cropping systems are dominant and productive.…”
Section: Grain Harvestcontrasting
confidence: 98%
“…'honestly, it's going in areas that are not of prime production for us, so it's a small part of the operation, a part of the operation that we are willing to sacrifice to experimentation' reflects the general sentiment of interviewed farmers about their decision-making process on Kernza location on their farms. This was consistent with expectations from annual grain farmers reported by Adebiyi et al (2015) that said they would plant perennial grains on under-utilized or marginal fields.…”
Section: Growing Kernza In the Marginssupporting
confidence: 89%
See 1 more Smart Citation
“…Both erosion reduction and on-farm benefits are related to farm characteristics (Table 7). The soil health theme was discussed in relation to practices like perennials, organic practice in general, cover crops, no-till, and rotational grazing (Adebiyi, Schmitt, and Snapp 2016;Bossange et al 2016;Brummel and Nelson 2014;Ulrich-Schad, Brock, and Prokopy 2017). The third most frequently coded benefit theme was off-farm benefits (n ¼ 11).…”
Section: Benefits Of Conservation Practices As a Motivationmentioning
confidence: 99%
“…Since perennial crops yield less than annual crops, efforts to develop perennial wheat have focused on improved grain yield (Cox et al, 2006, Jaikumar et al, 2012, Hayes et al, 2012). However, Adebiyi et al (2015) found that farmers in Michigan who experimented with perennial wheat described soil and environmental quality as their primary motivations for doing so. An emphasis on yield in a low-input, low-output developing country environment may not capture the tradeoffs perceived by farmers or the broader ecological benefits.…”
Section: Introductionmentioning
confidence: 99%